In Pursuit of a Shadow By a Lady Astronomer - Brown, Elizabeth (Cambridge University Press, 1888)
The title page calls the author of this 1888 work 'A Lady Astronomer'. She was Elizabeth Brown (1830–99), and the shadow she was pursuing was the eclipse of the sun on 19 August 1887, which could be best observed in northern Russia. Brought up by her father to make weather observations and to use a telescope, she became a member of the Liverpool Astronomical Society - on behalf of which she undertook her Russian expedition - and was later active in founding the British Astronomical Association. (The Royal Astronomical Society did not at this point admit women.) The book describes her journey, from her arrival at Hull to meet her travelling companion, to Russia, and home again. The actual viewing of the eclipse, at Kineshma, 200 miles north-east of Moscow, was spoiled by cloud cover, but her lively and observant account of her adventures is a fascinating record by a pioneering female scientist
Title from publisher's bibliographic system (viewed on 05 Oct 2015)